COGNITIVE FUNCTIONS CONDITION OF POST-STROKE PATIENTS - Gerasymchuk, V. R.; Uwa-Agbonikhena, I. F.; Maksymchuk, L. T.; Kupnovytska-Sabadosh, M. Yu.; Nehrych, T. I.; Doroshenko, O. O.; Sorokhman, A. V.; Genyk, S. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
60 patients after a hemispheric ischemic stroke (IS) were examined. Mini Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Frontal Assessment Battery (FAB), Trail Making Test A and B (TMT), and the Clock Drawing Test (CDT) were used for the cognitive status assessment. A decrease in the MMSE, FAB and MoCA score compared to the control group (CG) (p<0.05) was observed, with probable differences mainly in the domains of attention (p<0.05) and executive functions (p<0.05). An increase in the time of task execution by 45.5% was detected for TMT A (p <0.05) and 61.9% for TMT B (p <0.01), and violation of CDT performance compared to the CG (p<0.05). Thus, the study of cognitive status using TMT and CDT may be recommended for timely detection of the initial executive functions impairment.